A Comparative Study of the Oxidation of Benzoin by Thallium(III) Salts in Methanol Medium: A Kinetic and Mechanistic Approach - Chimatadar, S.A.; Salunke, M.S.; Nandibewoor, S.T. (Asian Journal of Chemistry, 2016)
A comparative study of the oxidation of benzoin by different thallium(III) salts in methanol medium is studied. The reaction is first order each in thallium(III), benzoin and acid concentrations. The effect of substituents is studied and the value of reaction constant (s) is obtained. Activation parameters for the oxidation of benzoin by different thallium(III) salts were evaluated and discussed. The proposed mechanism is consistent with the observed results.